Implementasi Framework Bootstrap 5 Pada Perancangan Front-End Website MC BRO di PT X - Perdana, Chepy; Maharani; Angga Wijaya, Masesa (Jurnal Sistem Informasi Galuh, 2024)
Abstract PT X has a manufacturing center division which is directly responsible for the production process (transfer load) of the products it produces, starting from the process of checking images of products to be produced, checking the completeness of production materials, reporting production progress, and reporting quality assurance checks. /quality assurance. The production process is still carried out manually and is considered less efficient because it is prone to errors in conveying information, the controlling process is not transparent, it takes a long time to access the files being worked on and it is difficult to find work history/drafts, so this division created an information system website-based with the name MC BRO which can make it easier for employees to monitor production activities. Along with its use, this information system continues to be developed according to the needs of employees, including in terms of appearance. To meet these needs, a Front-End design for the MC BRO website was created which was made according to the interface design that had been designed by the UI/UX designer into HTML, CSS and JavaScript program code. In the creation process, the Front-End design goes through a workflow, namely the process of needs analysis, literature study, implementation, revision and utilizing the classes in the Bootstrap 5 framework in order to speed up the process and produce a responsive and comfortable MC BRO website appearance to use, so that it can meet user needs in the display aspect.